BOBBY WALKER AS VICTIM OF CAPITALIST SYSTEM AS SHOWN IN THE COMPANY MEN MOVIE - GUNAWAN, LUCKY (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: workers discrimination, labor, capitalism, The Company Men movie. Workers discrimination threats society and causes social problem. One of the causes of the worker discrimination is capitalism. The movie entitled The Company Men reveals some causes and effects of worker discrimination caused by capitalism that affect the society inside the movie. This research applies Sociological approach as the main study to analyze this movie entitled The Company Men. This study also applies the concept of capitalism, industrial sociology and movie studies.The result of the study reveals that workers exploitation causes many effects to the society. In the movie The Company Men, Jim Salinger who becomes the main antagonist discriminates his workers for his own benefit. The workers discrimination causes many bad effects for Bobby Walker and the other workers such as jobless, suicide, and family problem. Those effects cause imbalance to the cycle of society which disrupt the life of labors.For future researchers, it is advisable to conduct further studies on thesame movie but with different approaches. One of the examples is Marxismapproach, because Marxism approach can be used to analyze the struggle of theBobby Walker and the other workers to survive.